Unravelling deservingness: Which criteria do people use to judge the relative deservingness of welfare target groups? A vignette-based focus group study. (October 2020) - Heuer, Jan-Ocko; Zimmermann, Katharina
Previous research suggests that European citizens share consistent attitudes towards the relative deservingness of different target groups of social policy, such as perceiving elderly people as most deserving, unemployed people as less deserving and immigrants as least deserving. Yet, it is unclear which criteria people apply when making these judgements. In this article, we explore the reasoning behind deservingness judgements. We analyse how four focus groups – from the middle class, the working class, young people and elderly people – discuss and rank various vignettes representing welfare target groups. Our focus groups' rankings mirror the well-established rank order of welfare target groups, and we also introduce further target groups: median-income families, low-income earners, and well-off earners. Our analyses of reasoning patterns show that depending on the target group specific combinations of deservingness criteria suggested in the literature (e.g. need, reciprocity, identity, control) are applied, and we suggest adding a further criterion emphasizing future returns on invested resources ('social investment'). Furthermore, by comparing focus groups, we find that different groups back up similar rankings by differing criteria, suggesting that below the surface of a 'common deservingness culture' linger class and other differences in perceiving welfare deservingness.